Judges' Considerations in Granting Permission to Underage Marriage Applications at the Luwuk Religious Court - N. A. Sustiono; Marzuki Marzuki; Sidik Ibrahim (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2022)
This study discusses judges’ considerations in granting requests for underage marriages permission at the Luwuk Religious Court. This study used a qualitative method. The data was collected through direct observation, in-depth interviews, and written document analysis. The data, then, was analyzed using thematic analysis to find themes from the data. The results of this study show that the procedure for submitting a marriage dispensation at the religious court is the same as the mechanism for filing other application cases. Increasing the minimum age for marriage for women to 19 years impacted the increase cases of underage marriage dispensation applications at the Religious Courts. The filing of a underage marriage dispensation case in the Religious Courts was caused by preventive and curative factors. The basis used by the judge in deciding the application for underage marriage dispensation is based on the theory of law enforcement. Then there must be considerations encouraging the judge to grant the application for underage marriage dispensations. The factors considered by judges in determining the dispensation of marriage were also related to psychological, health, educational, and economic factors. These four factors were taken into serious consideration by the judge in determining the dispensation of marriage. Based on the results, we recommend the religious courts should be more selective in examining, considering, and determining applications for underage marriage dispensation to prevent social conflicts and the impact of these decisions to society.